Efektivitas Peran Generasi Berencana dalam Meminimalisir Penyimpangan Sosial Remaja di Kecamatan Warureja Kabupaten Tegal - Arifin, Muhammad Jaenal; Hermanto, Fredy (Universitas Negeri Semarang, 2020)
Free sex and drug use are deviant behaviors that are often carried out by teenagers. Warureja Subdistrict is a place where, based on data from the P3A2P and KB Office, it is the area with the highest rates of free sex and drug use. The research method used is the mixed methods approach, namely by combining two forms of approach in research, namely qualitative and quantitative. The results of this study are: (1) The Role of Planning Generation in minimizing adolescent social deviation in Warureja District is included in the very high category of 53.28% or effective with effectiveness indicators: a) Work program 49.64%, and b) Independence of PIK R 89.05% . (2) The inhibiting factor of the genre in the high category is 71.53%, but the driving factor is higher because of the belief in the performance of the genre, namely 74.45%. (3) The role of the planning generation is to provide socialization and understanding to adolescents about the dangers of free sex and drug use, the importance of planning for the future (education, career, marriage, community life), providing life skill training, and collaboration with agencies and communities.